Implementation Of Association Technique In Identify The Frequent Pairing Subject From Private Tutor Data - Asnor, Nur Hamizah (2017)
In this project we are doing research on implementation data mining in big data. We have explored about Market Basket Analysis is that consist of the algorithm, technique and implementation method. In market basket analysis, normally we can identify the business study and research were focusing on the marketing and business domain. There are no research’s about education domain. So in this research, we would like to implement the market basket analysis in education domain. We would like to identify the frequent pairing request subject by customer. We are using real data that has been scrapped from online tuition website. The implementation process will be doing using rapid miner tools. An Apriori and Association algorithm was selected to implemented this project.